Insulin secretion and sensitivity during oral glucose tolerance test in Korean lean elderly women. - Kim, J. (Korean Academy of Medical Sciences, 2001)
Impaired glucose tolerance (IGT) and type 2 diabetes including undiagnosed isolated postchallenge hyperglycemia (IPH) are common in the elderly. The aim of this study was to investigate the insulin secretion and sensitivity in Korean elderly lean diabetic women. Forty-one lean women aged 65-88 years took 2 hr oral glucose tolerance test (OGTT) and were stratified according to the WHO criteria (normal glucose tolerance [NGT], n=20; IGT, n=6; and type 2 diabetics, n=15 including seven IPH). HbA1c and fructosamine progressively increased from the NGT to the diabetic subjects (p=0.006 and p=0.001, respectively). Compared with subjects with NGT, the insulinogenic index, a marker of early insulin secretion and the AUC(ins), a marker of total insulin secretion, decreased significantly in diabetic group [0.53 (-0.44 -1.45) vs. 0.18 (0.00 -1.11), p=0.03 and 306+/-165 vs. 199+/-78 pmol/L, p=0.02 respectively]. A significant difference was found in the AUC(c-peptide) among each group (221+/-59 vs. 206+/-34 vs. 149+/-51 pmol/L, p=0.001 for each). The homeostasis model assessment of insulin resistance (HOMA-IR), a marker of insulin resistance, was not different among the groups. We conclude that compared with NGT subjects, elderly lean women with diabetes have impaired oral glucose-induced insulin secretion but have relatively preserved insulin sensitivity. This suggests that insulin resistance is not necessarily an essential component of Korean elderly lean diabetic women.